Paternal preconceptional radiation exposure in the nuclear industry and leukaemia and non-Hodgkin's lymphoma in young people in Scotland. Issue 6886 (1st May 1993) - Kinlen, L J; Clarke, K; Balkwill, A
Abstract : OBJECTIVE--To determine if a relation exists between paternal exposure to relatively high levels of radiation in the Scottish nuclear industry and the risk of leukaemia and non-Hodgkin's lymphoma is subsequently conceived children. DESIGN--Matched case-control study with three controls for each case. SETTING--The whole of Scotland. SUBJECTS--The fathers of 1024 children with leukaemia and 237 children with non-Hodgkin's lymphoma diagnosed in Scotland below the age of 25 among those born in Scotland since nuclear operations began (in 1958) and the fathers of 3783 randomly chosen controls. The fathers of 80 children with leukaemia and 16 with non-Hodgkin's lymphoma in north Cumbria were also covered since some workers at one Scottish nuclear site live over the border in that area. Details of all fathers were then matched against records of the nuclear industry. MAIN OUTCOME MEASURES--Paternal preconceptional radiation exposures, particularly relatively high levels, both lifetime and in the six and three months before conception. RESULTS--No significant excess was observed in any subgroup and there was no significant trend: fathers of three controls but no cases were exposed to lifetime preconceptional levels of 100 mSv or greater (Fisher's exact p value 0.84). In the six months before conception, fathers of two cases and three controls received 10 mSv or more, odds ratio 2.3 (95% confidence interval 0.31 to 17.24). In the three months before conception the fathers of one case and two controls received 5 mSv or more, odds ratio 1.7 (0.10 to 30.76). The results for leukaemia and non-Hodgkin's lymphoma combined were similar. CONCLUSIONS--No significant excess of leukaemia or of leukaemia and non-Hodgkin's lymphoma was found at any radiation level in any preconceptional period.